Beating the urine drug test - a case report on niacin toxicity - Beenish Fayyaz; Hafiz J. Rehman; Sunita Upreti (Greater Baltimore Medical Center, 2018)
Niacin is a form of vitamin B3 which is used for the medical treatment of hyperlipidemia and niacin deficiency. However, within the last few years, it is being advertised on the Internet as a quick way to detoxify the human body in an attempt to evade urine drug tests. This claim is without any medical or scientific evidence and as a result, many cases have been reported where young adults have ended up with niacin toxicity. In this case report, we discuss a rare presentation of niacin toxicity and the effects Internet has had on the healthcare being practised by both the physicians and the patients themselves.